Pipette‐tip solid‐phase extraction based on deep eutectic solvent modified graphene for the determination of sulfamerazine in river water. Issue 9 (5th April 2017) - Liu, Lingling; Tang, Weiyang; Tang, Baokun; Han, Dandan; Row, Kyung Ho; Zhu, Tao
Abstract : A green and novel deep eutectic solvent modified graphene was prepared and used as a neutral adsorbent for the rapid determination of sulfamerazine in a river water sample by pipette‐tip solid‐phase extraction. Compared with conventional graphene, deep eutectic solvent modified graphene can change the surface of graphene with wrinkled structure and higher selective extraction ability. The properties of deep eutectic solvent modified graphene and graphene were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Static adsorption showed deep eutectic solvent modified graphene had a higher adsorption ability (18.62 mg/g) than graphene. Under the optimum conditions, factors such as kinds of washing solvents and elution solvents and volume of elution solvent were evaluated. The limits of detection and quantification were 0.01 and 0.03 μg/mL, respectively. The method recoveries of sulfamerazine were in the range of 91.01–96.82% with associated intraday relative standard deviations ranging from 1.63 to 3.46% and interday relative standard deviations ranging from 0.68 to 3.84%. Deep eutectic solvent modified graphene showed satisfactory results (recovery was 95.38%) and potential for rapid purification of sulfamerazine in river water sample in combination with the pipette‐tip solid‐phase extraction method.